GUIDELINE TO SOLVE TEACHER’S ACADEMIC PROCRATINATION OF PUBLIC UNIVERSITIES IN YUNNAN - Yuanni, Yang; Suteeniran, Niran; Dejhome, Pachara; Kaewsrimon, Buranajit; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
The purpose of this research were to 1) study the improvement of knowledge management capabilities of vocational and technological colleges in Yunnan Province; People’s Republic of China and 2) evaluate the characteristics of improving the knowledge management capabilities of vocational and technological colleges in Yunnan Province. People’s Republic of China.This research study uses a mixed methods research method. The population used in the research included administrators and regular teachers of vocational and technological colleges in Yunnan Province. People’s Republic of China, a total of 300 people. The research instrument is a 5 - level estimation scale questionnaire within 7 areas, consisting of 1) knowledge identification, 2) knowledge creation and acquisition, 3) knowledge organization, 4) knowledge processing and screening, 5) knowledge access, 6) exchange. Learn and 7) Learning, which has a reliability of .95. Statistics used in data analysis include percentages, means, and standard deviations. The results of the research found that 1) Improving the knowledge management ability of vocational and technological colleges in Yunnan Province. People’s Republic of China, including promoting personnel to learn and to use knowledge gained from training to create new work. morale boosting Opening opportunities to develop the potential of personnel to express their knowledge and abilities creatively for the organization and 2) Results of the assessment of characteristics for improving overall knowledge management ability. at a high level When considering each aspect, it was found that the greatest was learning (μ = 4.68, σ = 0.42), followed by the processing and filtering of identification knowledge. Creating and seeking knowledge Organizing knowledge into a system and the least is the aspect of access to knowledge. and exchange of knowledge respectively